Uncovering online travel agency antecedents and their consequences in terms of consumer behavior: A retrospective analysis for future research - Seema Singh; Prince Prince; Neha Aggarwal; Devika Dabas (Tourism)
The popularity of online travel agencies (OTAs) has been fueled by the growing use of internet technologies and the services they provide, and this makes it crucial to investigate consumer behavior (CB) towards them. The aim of the work is to identify the influencing factors/variables which affect CB and to provide empirical guidance on OTA antecedents and their consequences in terms of CB, based on a review of the existing literature using PRISMA protocol. An analysis of the 77 most pertinent articles has given a more thorough understanding of this revealing the most common influencing factors/variables (information, price, features, quality, customization & filters, user friendliness, etc.) used to measure the CB towards OTAs. Nevertheless, monetary value, trustworthiness, perceived value, website quality, electronic word of mouth (e-WOM), service quality and information value are the most common antecedents, with customer purchase intention, satisfaction and loyalty as major consequences in terms of CB. This article represents the first effort to conduct a thorough literature evaluation of the influencing factors/variables, antecedents and consequences for CB. A greater grasp of these three aspects in the tourism sector can be helpful to researchers and to managers in the hospitality industry as well.